PEMANFAATAN APLIKASI GOOGLE EARTH DALAM PEMBELAJARAN SEJARAH DI SMA NEGERI 4 KOTA JAMBI - Nikmah, Khoirun; Pamungkas, Satriyo (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2022)
The purpose of this study was to determine student responses to the application of the Google Earth application in history learning at SMK Negeri 4 Jambi City. The research that will be conducted is a descriptive quantitative research type because the researcher describes it based on the data that has been collected as it is. Based on the results of research that has been carried out regarding the use of the google earth application in history learning at SMA Negeri 4 Jambi City in class X 4. Based on the data from the student questionnaire as many as 35 people consisting of three indicators, namely indicators of interest, indicators of activity, and indicators of courage. In the interest indicator, an average percentage of 78.06% is included in the "Very Like" qualification. Furthermore, the second indicator, namely the indicator of student activity in learning, obtained an average percentage value of 76.91% which was included in the "Very Like" category. Next on the third indicator, namely the indicator of courage, it obtained an average percentage value of 72.86% which was included in the "Like" category. Thus, from the acquisition of the percentage values for the three indicators, it can be concluded that the use of the Google Earth application in history learning obtained an average percentage of 75.94% which was included in the "Very Like" classification.